2009
DOI: 10.1369/jhc.2009.953893
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Osteoarthritis in Humans Is Associated With Altered Collagen VI Expression and Upregulation of ER-stress Markers Grp78 and Bag-1

Abstract: ; and Summa Health Systems, Akron, Ohio (IG) S U M M A R Y To test the hypothesis that a perturbation of endoplasmic reticulum (ER) function is involved in the pathogenesis of osteoarthritis (OA), articular cartilage was isolated from non-OA patients secondary to resection of osteo-or chondrosarcomas. Intra-joint samples of minimal and advanced osteoarthritic cartilage were isolated from patients undergoing total knee arthroplasty and scored for disease severity. Glucose-regulated protein-78 (grp78) and bcl-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 51 publications
4
79
1
Order By: Relevance
“…31 Hallmarks of osteoarthritic cartilage are the degradation of ECM components and the destruction of this pericellular microenvironment. 32 Previous studies have shown increased amounts of COL6 in osteoarthritic cartilage, 33,34 depicting those modifications in the collagenous network that occur in degenerated cartilage. Our group has previously described an intracellular increase of this protein in OA chondrocytes.…”
Section: ' Discussionmentioning
confidence: 99%
“…31 Hallmarks of osteoarthritic cartilage are the degradation of ECM components and the destruction of this pericellular microenvironment. 32 Previous studies have shown increased amounts of COL6 in osteoarthritic cartilage, 33,34 depicting those modifications in the collagenous network that occur in degenerated cartilage. Our group has previously described an intracellular increase of this protein in OA chondrocytes.…”
Section: ' Discussionmentioning
confidence: 99%
“…When protein folding is disturbed, GRP78 synthesis is increased and GRP78 subsequently binds to misfolded proteins to prevent them from forming aggregates and assists them to refold properly [3]. Bag-1 has recently been shown to be a downstream regulator of ER stress in chondrocytes [4]. It is now well established that overexpression of Bag-1 protects chondrocytes from ER stress [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Bag-1 has recently been shown to be a downstream regulator of ER stress in chondrocytes [4]. It is now well established that overexpression of Bag-1 protects chondrocytes from ER stress [4,5]. Therefore elevated expressions of GRP78 and Bag-1 are considered to be reliable markers of ER stress [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, this protein occurs primarily in the pericellular matrix that surrounds the chondrocytes throughout the different zones. In OA cartilage, it was reported that the expression and overall distribution of type VI collagen increases in the lower middle and upper deep zones 45,46 . In the results presented in Fig.…”
Section: Discussionmentioning
confidence: 99%